2023
DOI: 10.3390/jimaging9030073
|View full text |Cite
|
Sign up to set email alerts
|

ARAM: A Technology Acceptance Model to Ascertain the Behavioural Intention to Use Augmented Reality

Abstract: The expansion of augmented reality across society, its availability in mobile platforms and the novelty character it embodies by appearing in a growing number of areas, have raised new questions related to people’s predisposition to use this technology in their daily life. Acceptance models, which have been updated following technological breakthroughs and society changes, are known to be great tools for predicting the intention to use a new technological system. This paper proposes a new acceptance model aimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 80 publications
(195 reference statements)
2
1
0
1
Order By: Relevance
“…This was reflected in the qualitative data through the category "Potential of the solution for training". As indicated in the results section and consistent with prior research Marto et al (2023) Alqahtani and Kavakli (2017), earlier studies have shown that both Performance Expectancy and Hedonic Motivation play a significant role in influencing Behavioral Intention (BI) to accept an AR system.…”
Section: Performance Expectancysupporting
confidence: 87%
See 1 more Smart Citation
“…This was reflected in the qualitative data through the category "Potential of the solution for training". As indicated in the results section and consistent with prior research Marto et al (2023) Alqahtani and Kavakli (2017), earlier studies have shown that both Performance Expectancy and Hedonic Motivation play a significant role in influencing Behavioral Intention (BI) to accept an AR system.…”
Section: Performance Expectancysupporting
confidence: 87%
“…As far as we know, there are no studies on AR acceptance models that specifically address Emotional Reaction, Realism, and Attention. However, Performance Expectancy and Hedonic Motivation, in line with the previous research of Marto et al (2023) and Alqahtani and Kavakli (2017), have been shown to influence Behavioral Intention (BI). This confirms that a stronger Performance Expectancy and participants' hedonic motivation, emphasizing pleasure and fun in using the system, lead to a stronger behavioral intention to use the system.…”
Section: Structural Modelsupporting
confidence: 81%
“…facilitating condition yang lebih tinggi atau memadai akan megarahkan pada niat penggunaan yang lebih tinggi untuk menggunakan JakOne Mobile. Semakin baik facilitating condition maka akan semakin kuat behavioral intention (Marto et al, 2021). Dalam hal ini penggunaan jakone mobile sangat terikat dengan sumber daya seperti smartphone dan koneksi internet (Tarhini et al, 2017).…”
Section: Pendahuluanunclassified
“…The technology acceptance model (TAM) is a widely used theoretical framework in the field of technology adoption and user behavior [35]. It aims to understand and predict individuals' acceptance and usage of new technologies.…”
Section: Technology Acceptance Modelmentioning
confidence: 99%